New Horizon of Intervention in Congenital Heart Disease: AFR in a Complex Cyanotic Patient - Zahra Khajali; Homa Ghaderian; Ata Firoozi; Zahra Hosseini; Maryam Aliramezany (Case Reports in Cardiology)
Double-inlet left ventricle (DILV) is the commonest form of the anatomic univentricular heart which has different ventriculoarterial connection; generally, the most prevalent type is DILV with the hypoplastic right ventricle on the left side. The disease is associated with several heart defects, and the treatment method is different based on the anatomy of the heart, but treatment methods are almost always palliative. In this paper, we described one adult patient with DILV and severe left AV (atrioventricular valve) stenosis who is managed with a novel palliative intervention; it means AFR (atrial flow regulator) device implantation for the first time.